Implementasi Aturan Ijin Mendirikan Bangunan (IMB) di Kawasan Sekitar Bencana Lumpur Sidoarjo - Nurul Agus Irawan; Arsiyah Arsiyah (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2016)
This study aimed to determine implementation of Sidoarjo Regulation Number 4 of 2012 on Building Permit (IMB) in Tambak Kalisogo village, Jabon subdistrict, Sidoarjo Regency. This study used qualitative research through descriptive approach. Informants in this study was village officials especially in community development field, community that was doing or newly building houses, community that have supporting data, the parties that have qualified in providing information, as well as data in BPPT Sidoarjo. The results of this study indicated that implementation of regulations concerning building permits in Tambak Kalisogo Village quite good. It was influenced by several factors, namely economic factors, customs were still strong and lack of socialization in the village government. While, supporting factor included encouragement the needs and compensatory of mudflow disaster victims.